What a difference a mom makes [compact disc, unabridged] : the indelible imprint a mom leaves on her son's life - Leman, Kevin (Oasis Audio, 2012)
Your boy wants to please you, and he cares deeply about what you think. Those driving needs will stay with him throughout his lifetime. That gives you, Mom, a lot of influence over your son. You can set him up for success in life. And the best news? It's never too late to start, no matter what age your son is now.